2004
DOI: 10.1038/nmat1242
|View full text |Cite
|
Sign up to set email alerts
|

Flash welding of conducting polymer nanofibres

Abstract: The absorption of light by a material generates heat through non-radiative energy dissipation and exothermic photochemical reactions. In nanostructured materials, the heat generated through photothermal processes will be confined within the individual nanostructures when heat transfer to neighbouring nanostructures and the environment is slow. This leads to unprecedented photothermal effects that cannot be observed in bulk materials, especially when a strong, pulsed light source is used. Here we demonstrate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
166
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(172 citation statements)
references
References 26 publications
5
166
1
Order By: Relevance
“…In fact, exposure to a camera flash transforms the Au nanocages (deposited on a carbon-coated TEM grid and surrounded by air) into spherical droplets. [24,31] In biological systems where water offers greater thermal conductivity, the Au nanocages should not melt but rather produce a local temperature rise that can provide a therapeutic effect on cancer cells that are selectively targeted by bioconjugated Au nanocages. Such photothermal therapy is less invasive than chemotherapy or surgery and holds strong promise as a new form of cancer treatment.…”
Section: Gold Nanocages For Photothermal Therapymentioning
confidence: 99%
“…In fact, exposure to a camera flash transforms the Au nanocages (deposited on a carbon-coated TEM grid and surrounded by air) into spherical droplets. [24,31] In biological systems where water offers greater thermal conductivity, the Au nanocages should not melt but rather produce a local temperature rise that can provide a therapeutic effect on cancer cells that are selectively targeted by bioconjugated Au nanocages. Such photothermal therapy is less invasive than chemotherapy or surgery and holds strong promise as a new form of cancer treatment.…”
Section: Gold Nanocages For Photothermal Therapymentioning
confidence: 99%
“…6 The radius of superstructures can be predicted by the simple equation suggested by J. K. Lim et al 4 The suggested equation, however, is valid only under limiting conditions. The equation is based on the assumption that the length of the PPy segment is comparable to, or much longer than the gold segment resulting in two almost parallel adjacent nanowires, or a very small angle, α, between the adjacent PPy segments (Figure 1).…”
Section: -3mentioning
confidence: 99%
“…Recently, an elctrospinning technique 73,74 has been shown to be effective to produce pure polymer and polymer nanocomposite fibres with diameters in the range of 200 nm to 300 nm. More interesting is, in electrospun nanocomposite fibres, the nanoparticles were found to be highly aligned.…”
Section: High Performance Fibre/fabricsmentioning
confidence: 99%
“…Using a mask, fibres can be joined in any desired pattern 73 . Such materials may find wide applications in defence as electrically conductive fabrics, sensors, electromagnetic shielding, microwave absorption, electrical energy storage (capacitors), actuators, and materials for micro UAVs.…”
Section: High Performance Fibre/fabricsmentioning
confidence: 99%